From screen culture to vision – some results of a disobedient epistemic approach - Costa, Pedro Rodrigues (2014)
It is known that different types of screens and their different uses have caused remarkable behavioral and social differences. Most studies originates from North America, focused mainly on the use of the TV. Recently, the relationship between the uses of TV and the Internet has allowed uses dynamic comparisons, revealing marked differences in a behavioral, social and cultural level. This article presents some results of a doctoral thesis comparing young and adult users of various types of screens (Cinema, TV, Computers, Tablets and Smartphones) with only TV young and adult users. This comparison in individuals with similar socioeconomic profiles, indicted significant qualitative differences in terms of learning, thinking, the uses of memory, the processes of socialization and individuation of archetypes. The comparison is justified due to the use of TV by the Portuguese, which corresponded, on average, 215 minutes per day between 2000 to 2008. This term became a stable value, in general, while younger (between 4 and 14 years) have decreased visualization to 180 minutes due to a greater use of the Internet. The comparison performed here was based on these data, however relying on a qualitative methodology, whether through speeches either in conjunction with data from other studies. The results indicate that the use of more different types of screens (TV, Internet, Smartphones and Tablets), compared with those who only use the classic TV screen, tends to lead to differences in the predisposition to learning and critical stance in relation to information.